Peptides Derived From Mismatched Paternal Human Leukocyte Antigen Predicted to Be Presented by HLA-DRB1, -DRB3/4/5, -DQ, and -DP Induce Child-Specific Antibodies in Pregnant Women - Niemann, Matthias; Matern, Benedict M.; Spierings, Eric; Schaub, Stefan; Hönger, Gideon (Frontiers in Immunology, 2021)
Predicted Indirectly ReCognizable Human Leukocyte Antigen (HLA) Epitopes (PIRCHE) are known to be a significant risk factor for the development of donor-HLA-specific antibodies after organ transplantation. Most previous studies on PIRCHE limited their analyses on presentation by the HLA-DRB1 locus, although HLA-DRB3/4/5, -DQ and -DP are also known for presenting allopeptides to CD4+ T cells. In this study, we analyzed the impact of predicted allopeptides presented by these additional loci on the incidence of HLA-specific antibodies after an immunization event. We considered pregnancy as a model system of an HLA immunization and observed child-specific HLA antibody (CSA) development of 231 mothers during pregnancy by samples being taken at delivery. Our data confirms PIRCHE presented by HLA-DRB1 along with HLA-DRB3/4/5, -DQ and -DP are significant predictors for the development of CSA. Although there was limited peptidome-overlap observed within the mothers’ presenting HLA proteins, combining multiple presenting loci in a single predictor improved the model only marginally. Prediction performance of PIRCHE further improved when normalizing scores by the respective presenters’ binding promiscuity. Immunogenicity analysis of specific allopeptides could not identify significant drivers of an immune response in this small cohort, suggesting confirmatory studies.